Traumatic avulsion of the globe with optic nerve transection: an unusual presentation. Issue 10 (29th October 2020) - Meena, Seema; Rakheja, Vaishali; Sahu, Sulabh; Rathore, Priyanka
Abstract : Complete globe extrusion, whether traumatic or spontaneous, is a rare clinical entity and if associated with optic nerve avulsion, it has a worse visual outcome, though repositioning of the globe may be attempted. We report a case of road traffic accident, wherein the patient presented with an extrusion of the globe, along with a complete transection of the optic nerve, about 4 cm from the optic nerve head, with only a residual attachment to the orbital rim via the unsevered lateral conjunctival flap, where the enucleation was completed and the conjunctiva was sutured.